Discussion on the realization technology of virtual hacker robot - Yuehong, Zhang (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
Virtual hacker robot is a new mode of security control detection in the network security industry. The detection service of security control is gradually changing from manual service to robot service to alleviate the current shortage of security professionals. This paper compares the problems existing in the traditional security management methods and protection means, combined with artificial intelligence technology and penetration testing technology, expounds a number of functions that virtual hacker robot can achieve, such as: asset detection, vulnerability utilization, security verification, risk quantification, etc. Finally, we analyzes the problems and challenges of virtual hacker robot technology.